Human Resource Competence Through the Application of the People Capability Maturity Model to the Competitive Advantage of Human Resources - WIDYAWATI, Sapta Rini; WIRAYANTI, Ni Kadek Sinta; SARI, Ni Kadek Meilda Dwiarta (Integration: Journal Of Social Sciences And Culture, 2025)
Purpose:In the face of global challenges and rapid technological developments, organizations are required to have a superior human resource management (HR) strategy in order to achieve sustainable competitiveness. The People Capability Maturity Model (PCMM) is present as a framework that helps organizations develop HR competencies systematically through five levels of maturity. This study aims to examine the relationship between the application of PCMM and the improvement of human resource competence and the competitive advantage of human resources.Methodology:The sample consisted of 180 respondents who worked for retail companies in Bali. The approach used was quantitative, with data collection through online questionnaires and limited interviews, which were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method.Findings:The results of the study show that the implementation of PCMM has a significant effect on improving employee competence. Human resource competence has also been proven to have a significant direct influence on the competitive advantage of human resources. In addition, the influence of PCMM on competitive advantage is indirect through the mediation of human resource competencies.Implication:These findings reinforce the Resource-Based View (RBV) theory which emphasizes the importance of internal capabilities as a source of competitive advantage. The implications of this study emphasize the importance of companies to align HR development strategies with maturity models such as PCMM.